An investigation of microstructure and sliding wear in thermally sprayed WC-Co coatings - Sudaprasert, Tippaban (2002)
Four types of WC-Co cermet powders (conventional WC-12 wt% Co, two different types of conventional WC-17 wt% Co and nanoscale WC-12 wt% Co powders), which have differences in terms of Co content, powder manufacturing process and WC grain size, have been sprayed to form coatings with both the high velocity oxygen-gas fuel (HVOGF) and the high velocity oxygen-liquid fuel (HVOLF) processes. The carbide grain size, powder particle size distribution and phase volume fraction of the starting powders were measured. The as-sprayed coatings were characterised by optical microscopy (OM), scanning electron microscopy (SEM), xray diffraction (XRD), transmission electron microscopy (TEM) and microhardness and surface roughness measurements.